Configuration management : implementation, principles and application for manufaturing industries - Sorrentino, Joseph (CRC Press, 2009)
"This valuable guide emphasizes that configuration management is driven by designers, not by the often unpredictable whims of end-users. It also addresses ways to overcome lost tribal wisdom - the tendency to fall into the new-newer-newest syndrome, always looking for the next great technology, software, and so on." "This text effectively provides the knowledge base industrial, project management, and lean engineers need to learn, implement, and apply the tried-and-trusted strategies of configuration management in any company."--BOOK JACKET